Influencia de la dosificación del mucílago de la planta Prosopis Pallida sobre la velocidad de corrosión del acero ASTM A335 P11 en HCl 1M a temperaturas de 25ºC, 45ºC y 65ºC. - Carrasco Muñoz, Juan Diego (2023)
ABSTRACT The mucilage from the seeds of Prosopis pallida (MPP) as a cheap and ecological source was used to prepare a novel green corrosion inhibitor for P11 steel in an acid medium. The inhibition efficiency of MPP was evaluated by potentiodynamic polarization, polarization resistance, electrochemical frequency modulation, and electrochemical impedance spectroscopy. Considering the four techniques used, an average maximum inhibition efficiency of 80.3% was achieved at 65 °C using 140 ppm of MPP. It was found that the inhibition efficiency and the equilibrium constant of adsorption increased with increasing temperature. The standard enthalpy of adsorption was positive and the apparent activation energy decreased with increasing concentration of MPP. All these parameters indicate that the adsorption of MPP on the surface of P11 steel occurs through chemical adsorption. Furthermore, MPP acts as a mixed-type inhibitor and the results obtained show that it has a high capacity to reduce acid corrosion, particularly at high temperatures